A Study of School Culture in Secondary Schools of District Swat Khyber Pakhtunkhwa, Pakistan (Journal of Social Sciences Review, 2022)
Schools’ culture is a key indicator for schools’ effectiveness andoverall activities of the school. Its influence is much more significant at the levelof secondary schools that are having the duty for the provision of qualitygraduates to institutions of higher education and skilled people to the jobmarket. School culture consists of norms, beliefs, principles, rituals andbehaviors which designs the rules of thinking, feelings and action inside aneducational organization and ultimately influences school performance. Havingthe significant role of school culture in the background, the study aimed toinvestigate the school culture at secondary level. The objectives of the studywere; to investigate the schools’ culture at secondary level and recommendstrategies for the improvement of school culture in secondary schools. Thedesign of the study was quantitative descriptive survey. The population of thestudy was 162 male heads of secondary schools in District Swat. The researcherselected a sample of 118 heads through simple random sampling, developed aLikert questionnaire, validated it and pilot tested for the determination of itsreliability. The data were gathered through self-administered questionnairesfrom the respondents and analyzed with mean scores, standard deviation andChi-square test. The study found a positive school culture with clear chalked outvisions and missions, heads of the school took initiatives for achieving the visionof schools, teachers themselves prepared the rules for functioning of the schoolsand the head and teachers had collegiality for achieving schools’ visions. Theadministration of the schools were ambitious, friendly and supportive for thestudents, democratic in decision making, resolved the problems of teachers andstudents and were competent enough to satisfy the needs of the schools,teachers worked for the academic excellence of their students, regularly assessedstudents’ academic progress, focused on co-curricular activities and observedpositive human relationship. It further forwarded recommendations for theimprovement of the school culture at secondary level.
Keywords: School Culture, Secondary Schools, District Swat Khyber Pakhtunkhwa, Pakistan